2012
DOI: 10.1016/j.ridd.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Parent–infant interaction in infant siblings at risk of autism

Abstract: Recent models of the early emergence of autism spectrum disorder (ASD) propose an interaction between risk susceptibility and the infant's social environment, resulting in a progressively atypical developmental trajectory. The infant's early social environmental experience consists mostly of interaction with caregivers, yet there has been little systematic study of early parent-infant interaction in infants at risk of ASD. This study examined the global characteristics of parent-infant interaction in 6- to 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
1
19

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 54 publications
16
150
1
19
Order By: Relevance
“…More recently, we have observed how this interactive style is part of a more general deficiency in interactive reciprocity characterized by reduced motor activity, fewer vocalizations, asynchronous vocal-motor patterns in the child, and less involvement and less use of 'affectionate touch' in the parents . Our results are in line with other recent studies on siblings of children already diagnosed (Wan et al, 2012), and could have important repercussions regarding the role that has been attributed to parent-mediated treatments, which are aimed at enhancing supportive interactions in everyday life (Oono, Honey, & McConachie, 2013).…”
Section: Parent-infant Interaction In the Home Movies Of Infants Withsupporting
confidence: 91%
“…More recently, we have observed how this interactive style is part of a more general deficiency in interactive reciprocity characterized by reduced motor activity, fewer vocalizations, asynchronous vocal-motor patterns in the child, and less involvement and less use of 'affectionate touch' in the parents . Our results are in line with other recent studies on siblings of children already diagnosed (Wan et al, 2012), and could have important repercussions regarding the role that has been attributed to parent-mediated treatments, which are aimed at enhancing supportive interactions in everyday life (Oono, Honey, & McConachie, 2013).…”
Section: Parent-infant Interaction In the Home Movies Of Infants Withsupporting
confidence: 91%
“…Manchester Assessment of Caregiver-Infant Interaction (MACI) (Wan et al, 2012(Wan et al, , 2016 This validated rating scale measure of global qualities of parent-infant interaction is suitable for 3-15 months of age and was designed to measure seven key areas on a 1 to 7 scale based on 6 minutes of videotaped unstructured play (Wan et al, 2016). A trained coder, who has undergone >70 hours training and supervised coding practice, rated the videotaped interactions following detailed reviews and narrative notes of the play episode, blind to family information and study aims.…”
Section: Methodsmentioning
confidence: 99%
“…Atzil et al, 2011;Strathearn et al, 2009;. Secondly, selection of the HSMs and LSMs was initially determined by taking ratings of 1+ above the SD (ratings 5-7), and 1+ below the SD (ratings 1-2) (Wan et al, 2012). However, as this did not provide, the required number of 15 in each group the thresholds were increased, but with no overlap.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…They found that the mothers had less emotionally synchronized interactions with their infants compared with mothers in the control group; however, there was no significant impact of these subtle differences in interaction style on later language development, assessed when the infants were 14 months old. Wan et al (2012Wan et al ( , 2013 have reported that caregivers of high-risk infants were rated as more directive and less sensitive during play interactions with their 6-and 12-month-old infants compared with caregivers of low-risk infants. In these studies, the influence of caregiver-infant interactions on child language were not reported, only the relationship to later diagnoses of ASD.…”
Section: Studies Of Maternal Behaviormentioning
confidence: 99%